Energy analysis of biomass from agricultural waste - Chong, Kok Hing (Universiti Malaysia Sarawak, UNIMAS, 2006)
This main idea of this thesis is to perfor m an exergy analysis of biomass on agricultural wastes. Exergy analysis is a powerful tool to figure out how much energy is destroyed not only in quantity but in quality as well. Thus engineer can improve the combustion system by minimize t he energy dest royed. This exergy analyses were perform on bomb calorimeter, as a prototype for other closed system. Before perform exergy analysis, experiments were conducted on few agricultural wastes in natural state and dry state to determine its heating value. Th e equation in this analysis can be use to perform exergy analysis in any closed system.